Competency of Nursing Care Women’s Cervical Cancer - Intarasomwang, Chareassri; Srisawad, Kanjana (KASEM BUNDIT JOURNAL, 2019)
Cervical cancer is the second only breast cancer. 85% are found in developing countries. Cervical cancer remains an important public health problem in Thailand. The main cause of cervical cancer is the human papillomavirus (HPV) infection. The primary screening by Pap smear in early detection of cervical cancer. Prevention cervical cancer by vaccinating HPV. Radiation therapy and chemotherapy makes cervical cancer patients more likely to survive, reduced complications and quality of life. Competency of Nursing to development, manage and supervise cervical cancer patients with complex health problems, collaborate with health team members, empowerment Including clinical counseling for cervical cancer patients, leadership change for improving cervical cancer nursing practice, use of knowledge, theory, principles, ethical decision in operation, use empathic evidence to cure cervical cancer. It can cause cervical cancer survivors, decreased complications and quality of life.